Helicobacter Pylori Seropositivity and Acute Myocardial Infarction - Abdul-Gafour, Wathiq K.; Baqir, Haitham I; Al-Raubyee, Riyadh S (AL-Kindy College Medical Journal, 2011)
Background: Acute myocardial infarction (AMI) is one of the most common diagnoses in hospitalized patients. The stimulus that initiates the acute inflammatory process in AMI has not been identified. Conventional risk factors account only for approximately half of the patients with clinically apparent atherosclerosis which can leads to AMI. Recently a potential link between infectious agents and atherosclerosis has been suggested Objective: To find a possible association between Helicobacter pylori (H. Pylori) infection and AMI. Method: We studied the prevalence of antiH. pylori antibodies in 94 patients who were admitted with the diagnosis of AMI and a similar number of healthy individuals who were age and sex matched. This was done using ELISA technique. Results: Overall prevalence of anti-H. pyroli antibodies in patients with AMI was 82.9% whereas the prevalence in the control group was 78.7% . This difference yielded an odd ratio of 1.317. Chi square test shows that this difference was insignificant statistically (p-value 0.458) Conclusion: We feel that our results do not support the hypothesis which stated that chronic infection with H. pylori is a major risk factor for AMI.